Complete guide for exporters - Sharma, G. D. (Gopal Datt), 1912- (Press & Publications Agency : distributors, Thomson Press India, Publication Division, 1975)
On Indian foreign trade promotion, with abstracts of foreign trade regulations of the Govt. of India.